The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1242/dev.01842
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Wnt/β-catenin signaling during gastrulation using RNA interference in mouse embryos

Abstract: Generation of mutant mice and genotypingCytokeratin 19 (K19) promoter-driven Cre mice (K19-Cre) were previously generated by a knock-in of the Cre recombinase gene into the ATG translation initiation codon of exon1 of K19 (Harada et al., 1999). The β-catenin floxed (flox) allele and the β-catenin floxed deleted (floxdel) allele were previously described (Brault et al., 2001). K19-Cre mice were mated with β-catenin floxdel mice and the offspring, which inherited both alleles, were crossed with homozygous β-cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 52 publications
8
71
2
Order By: Relevance
“…Thus, in differentiated cells, we speculate that Dab2 maintains the differentiated state and restrains proliferation through its negative regulation of Wnt signaling, whereas in the proliferative state, Wnt attenuates expression of its inhibitor to maintain proliferation and block induction of the differentiation state. These results are consistent with a recent report (Lickert et al, 2005) demonstrating that Dab2 gene expression is upregulated in conditional b-catenin mutant mouse embryos, suggesting that not only is Dab2 a Wnt/b-catenin target gene, but that b-catenin signaling leads to its attenuation. In many intestinal neoplasias, constitutive Wnt signaling (Gregorieff and Clevers, 2005) and aberrantly low levels of Dab2 protein (Kleeff et al, 2002;Prunier et al, 2004) are often observed.…”
Section: Dab2 and Wnt Signaling Y Jiang Et Alsupporting
confidence: 93%
“…Thus, in differentiated cells, we speculate that Dab2 maintains the differentiated state and restrains proliferation through its negative regulation of Wnt signaling, whereas in the proliferative state, Wnt attenuates expression of its inhibitor to maintain proliferation and block induction of the differentiation state. These results are consistent with a recent report (Lickert et al, 2005) demonstrating that Dab2 gene expression is upregulated in conditional b-catenin mutant mouse embryos, suggesting that not only is Dab2 a Wnt/b-catenin target gene, but that b-catenin signaling leads to its attenuation. In many intestinal neoplasias, constitutive Wnt signaling (Gregorieff and Clevers, 2005) and aberrantly low levels of Dab2 protein (Kleeff et al, 2002;Prunier et al, 2004) are often observed.…”
Section: Dab2 and Wnt Signaling Y Jiang Et Alsupporting
confidence: 93%
“…Moreover, we can find little evidence for striped expression of Wnt/␤-catenin reporters in wild-type PSM, either at the protein or RNA level (Nakaya et al, 2005) (not shown), suggesting that ␤-catenin activity itself does not oscillate. Since only a small subset of Wnt/␤-catenin target genes oscillate, out of a much larger number of target genes (Dequeant et al, 2006;Lickert et al, 2005;Morkel et al, 2003) (our unpublished data), it appears that additional regulatory inputs are required for the oscillation of select Wnt target genes. The functional significance of oscillating Wnt target gene expression is not currently well understood.…”
Section: Discussionmentioning
confidence: 87%
“…1I-K). A faint signal was present as early as the mid-streak stage and expression became stronger along the primitive streak at the latestreak stage (7.25 dpc; Lickert et al, 2005). Between 7.5 and 8 dpc, Prtg and Punc expression patterns were very similar (Fig.…”
Section: Conservation Of Prtg Early Expression Between Vertebratesmentioning
confidence: 84%